The Ottoman Twilight in the Arab Lands - Deringil, Selim.
1 online resource (272 pages)
Keywords: This book provides an annotated translation of memoirs of Ottoman eye-witness actors of the Great War in the Arab lands. It reflects on numerous crises of the Middle East today such as the ambiguous Arab-Turkish relations, the Arab-Israeli confrontation, and the struggle for the holy places of Islam.